PSYCHOLOGICAL FEATURES OF INTERCOSSIBLE COMMUNICATION IN CONDITIONS OF PENITENTIAL UNIVERSITY - Makogonchuk, Evgeniya Sergeevna (Psychological Prospects Journal, 2013)
The article reveals the psychological specificity of communication in a penitentiary institution. In the context of the coverage of the specifics of the personnel of the correctional labor institution and the extreme nature of the stay of convicts in conditions of social deprivation of prisons, their interpersonal interaction was analyzed.